S-BPM Illustrated: A Storybook about Business Process Modeling and Execution - Fleischmann, Albert (Springer Nature, 2013)
Information Systems Applications (incl.Internet); Business Information Systems; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems